PENGARUH INVESTASI, TINGKAT HUNIAN DAN RETRIBUSI DAERAH TERHADAP PAD DAN IPM KABUPATEN/KOTA DI PROVINSI BALI - Jihansyah, Muhammad Syaifuddin; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Being popular tourist destinations encourages Bali to always strive for welfare of its people that can be seen from Human Development Index. Purpose of this study is to analyze the effect of investment, hotel occupancy rates and local user fees on regional original income and development indices and find out local revenue mediate in effect of investment, hotel occupancy rates, regional user fees on human development index in Bali. Secondary data with 72 observations using path analysis was used. Results showed, investment had no significant effect on regional original income, hotel occupancy rates and regional fees had significant effect on regional original income and human development index, regional retribution had no significant effect on the human development index. Local own income mediates the effect of hotel occupancy rates and local user fees on the human development index, while regional own income doesnot mediates effect of investment on human development index. Keywords: investment, hotel occupancy rate, regional retribution, local original income, and human development index